Riong Poetry Night ingnited a synergy of new generation - UMP, PNC
Some 3,000 undergraduates including those from AMIK Tunas Bangsa, Indonesia turned up to be mesmerized by singers and poets performing a variety of poetic songs and lyrical poems during the Riong Poetry Night organised by Berita Harian and Universiti Malaysia Pahang (UMP) at the Sports Complex in Gambang on March 9, 2012.